A qualitative study into female sex workers' experience of stigma in the health care setting in Hong Kong - Haixia Ma; Alice Yuen Loke (BMC, 2019)
Abstract Background Hong Kong has gained a good reputation for its quality public health care services. However, there is a growing recognition that social stigma is a potential obstacle when female sex workers (FSWs) access health care services. There are a lack of studies focusing on how FSWs experience and cope with stigma when accessing health care services in Hong Kong. Objective This study aims to explore how FSWs experience stigma and develop coping strategies when accessing health care services in Hong Kong. Methods This is a qualitative interview study. Staff of non-governmental organizations (NGOs) that serve sex workers in Hong Kong facilitated the process of recruiting the participants. In-depth individual interviews were conducted with 22 FSWs, focusing on their experiences of stigma and coping strategies when accessing health care services. A directed content analysis approach was adopted to analyze the data. Results The interview data can be grouped into three themes: experience of stigma in the health care setting; coping with the stigma of sex work; and the call for non-judgmental holistic health care. Conclusion This study contributes to an understanding of the experience of stigma and stigma coping strategies of FSWs when accessing health care services in Hong Kong. stigma remains an important issue for a large proportion of FSWs when they seek timely professional help, openly disclose their sex work identity, and receive comprehensive health care services. The study also highlights the need to address multiple healthcare needs of FSWs beyond STDs. Moreover, the study contributes to increasing awareness of, and respect for, the human right of FSWs to receive non-discriminatory health services.